Islanding detection in distributed generators using GBDT-JS techniques - Krishna Goriparthy Murali; Balakrishnan Geethalakshmi (Science and Technology for Energy Transition, 2023)
Renewable Energy Sources (RES) using PV arrays are considered and extensively employed in today’s world. Islanding is an issue that happens when The RES is connected to the grid and unexpected circuit breakers are connected to the grid trip. It is necessary to notice the islanding condition in two seconds according to IEEE standards. This manuscript proposed an effectual hybrid system for islanding detection of Solar PhotoVoltaic (SPV) based distributed generation system. The proposed technique is a hybrid combination of Gradient Boosting Decision Tree (GBDT) and Jelly Fish Search algorithm (JS) known as GBDT-JS Techniques. The main concept of this paper is to diminish the Non‐Detection Zone (NDZ) and maintain output power quality. These objectives are achieved by the proposed hybrid technique considering the Rate Of Change Of Frequency (ROCOF) at the target DG position is employed by the input assigned for the RF system in intelligent islanding detection. Here, Discrete Wavelet Transform (DWT) is employed for extracting intrinsic features among islanding and grid disturbance along GBDT. Also, the JS algorithm is used in the classification of islanding and grid disturbance. To find the feasibility of the proposed system various conditions such as different loads, switch operation, and network conditions are tested. In the validation of the proposed system MATLAB/Simulink working platform is utilized.